1978
DOI: 10.1128/aac.13.6.1044
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Three 8-Hydroxyquinoline Derivatives Against In Vitro Dental Plaque

Abstract: Three 8-hydroxyquinoline derivatives, assessed using an in vitro preformed dental plaque model system, were differentially inhibitory for four plaque-forming microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Antimicrobial effects of 8HQ and its derivatives encompassing antibacterial,102104 antimalarial,105107 antiviral,108 antitubercular,109 and antidental plaque activities110,111 have been previously reported.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Antimicrobial effects of 8HQ and its derivatives encompassing antibacterial,102104 antimalarial,105107 antiviral,108 antitubercular,109 and antidental plaque activities110,111 have been previously reported.…”
Section: Introductionmentioning
confidence: 93%
“…The result showed that all 8HQ derivatives differentially inhibited each of the tested organisms 111. These compounds were prepared in percentage concentrations in polyethylene glycol owing to their sparingly water-soluble nature 111. CQ and 5,7-dichloro-8HQ exerted a bactericidal effect at 0.05% concentration on S. mutans (cariogenic) and A. viscosus (periodontogenic), whereas 8HQ sulfate showed a bacteriostatic effect against both pathogens at a higher (0.3%) concentration 111.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations